Permasalahan Gender Dalam Konsep Nusyuz - Tenri Nayyara Nurnaina; Syahrur Rahmat; Tri Layla Salehah; Kurniati (Al-Qolamuna: Journal Komunikasi dan Penyiaran Islam, 2025)
Gender issues in the context of the concept of nusyuz are often linked to the issue of domestic violence (DV) occurring in society. Nusyuz, which literally means disobedience or non-compliance, is often misunderstood as merely a wife's disobedience, which is then used by some husbands to justify physical or psychological violence. However, the concept of nusyuz can actually refer to disobedience or defiance by both the wife and husband in fulfilling marital commitments, therefore this concept needs to be reinterpreted fairly from a gender perspective. In the context of domestic violence, justifying violence using nusyuz contradicts the principles of justice in Islam and the national legal framework, particularly Law Number 23 of 2004 concerning the Elimination of Domestic Violence, which states that there is no justification for domestic violence. This study highlights how patriarchal culture and gender-biased textual interpretations reinforce otherwise unlawful violent practices, and how nusyuz is often misinterpreted as granting husbands the right to beat their wives. This research encourages readers to understand nusyuz not merely as a symbol of a wife's disobedience, but as a form of protest against injustice and arbitrariness in the household, as well as the importance of peaceful, non-violent resolution. Efforts to eliminate patriarchal hegemony and promote gender equality are key to addressing the problem of domestic violence, which is often associated with the concept of nusyuz. Abstrak kekerasan dalam rumah tangga (KDRT) yang terjadi di masyarakat. Nusyuz, yang secara harfiah berarti pembangkangan atau ketidakpatuhan, sering disalahpahami sebagai pembangkangan istri semata yang kemudian dijadikan pembenaran oleh sebagian suami untuk melakukan kekerasan fisik atau psikologis. Namun, konsep nusyuz sebenarnya dapat merujuk pada ketidakpatuhan atau pembangkangan baik dari istri maupun suami dalam memenuhi komitmen perkawinan, sehingga konsep ini perlu direinterpretasi secara adil dari perspektif gender. Dalam konteks KDRT, justifikasi kekerasan dengan alasan nusyuz bertentangan dengan prinsip keadilan dalam Islam dan juga dengan kerangka hukum nasional, khususnya Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan dalam Rumah Tangga, yang menyatakan bahwa tidak ada alasan pembenaran untuk kekerasan dalam rumah tangga. Studi ini menyoroti bagaimana budaya patriarkis dan tafsir tekstual yang bias gender memperkuat praktik kekerasan yang seharusnya tidak terjadi, serta bagaimana nusyuz seringkali keliru dimaknai sebagai memberikan hak suami untuk memukul istri. Penelitian ini mengajak pembaca untuk memahami nusyuz bukan sebagai simbol ketidakpatuhan istri semata, melainkan sebagai bentuk protes atas ketidakadilan dan kesewenang-wenangan dalam rumah tangga, serta pentingnya penyelesaian yang damai tanpa kekerasan. Upaya penghapusan kultur hegemoni patriarkis dan kesetaraan gender menjadi kunci utama dalam mengatasi masalah kekerasan dalam rumah tangga yang kerap terkait dengan konsep nusyuz.